Systematic, noninvasive endometriosis diagnosis in transvaginal sonography by the Swiss Society of Ultrasound in Medicine - Metzler, Julian Matthias; Finger, Leana; Burkhardt, Tilo; Hodel, Markus Eugen; Manegold-Brauer, Gwendolin; Imboden, Sara; Pape, Janna; Imesch, Patrick; Witzel, Isabell; Bajka, Michael (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
We present a new systematic, comprehensive, checklist-based sonographic assessment of endometriosis in the female true pelvis. Emphasis is placed on practical skills teaching. The newly introduced White Sliding Line (WSL) is the core structure. The WSL separates five compartments (anterior, central, posterior, and lateral right and left) containing dedicated endometriosis signs of mobility and morphology to be checked. This approach relies on the 2016 IDEA Consensus and further developments. It directly connects to the 2021 #ENZIAN Classification Standard. In practice, evaluation follows the proposed checklist in all compartments, judging first sliding mobility between organs and structures in a highly dynamic investigation. A rigorous search for deep endometriosis (DE) is then performed. We treat adhesions due to their great clinical importance and possible, reliable diagnosis by TVS as the fifth endometriosis unit, next to endometrioma, DE, adenomyosis, and superficial endometriosis. Including superficial (peritoneal) endometriosis is a future goal.
Keywords: endometriosis; ultrasound; transvaginal; sonography; classification